PENAMBAHAN KARBON AKTIF SERBUK GERGAJI KAYU JATI DAN KAYU AKASIA TERHADAP FILTRATION LOSS DAN RHEOLOGI LUMPUR PEMBORAN - Maykel Gratia Toding (INFO-TEKNIK, 2026)
ABSTRACK Mud is a circulating fluid commonly used during the drilling process to provide various functions. Mud rheology and filtration loss are physical properties that must be controlled because they can help control formation pressure. Controlling fluid loss is essential during drilling to maximize cutting lift, prevent kicks, and minimize mud costs. To achieve appropriate filtration loss and rheology results, additives are needed in the drilling mud. One such additive is activated carbon, an environmentally friendly adsorbent widely used in industrial companies. Teak and acacia sawdust, which are waste from cutting furniture or furniture that is rarely used, are then utilized to make activated carbon. Teak wood has a cellulose content of 40.26-43.12%, hemicellulose 27.07-31.97% and lignin 24.74-28.07%. Acacia wood has a cellulose content of 51.46% with a lignin content of 27.66%. The stages of making sawdust activated carbon include dehydration, carbonization, and activation. Then, it is added to drilling mud with a composition of 4 grams, 7 grams, and 10 grams of activated carbon to determine the filtration loss and rheology values of the drilling mud. Based on the test results, it was obtained that the values of plastic viscosity, yield point, gel strength, filtration loss, pH, mud cake, and density met the API 13A standard, but for the densities of 7 grams and 10 grams of acacia sawdust did not meet the API 13A standard. Keywords: Rheology, Filtration Loss, Activated Carbon, Teak and Acacia Sawdust.